Do palácio à periferia: a trajetória do Colégio Universitário da UFMA (1980-2006) - OLIVEIRA, Wilson Raimundo de (2019)
This research aims to analyze the trajectory of the University School (COLUN / UFMA), in order to understand the nature of its installation, operationalization and consolidation as a school form, specific school culture and unique institution and focuses of its educational action on São Luís' suburb - Vila Palmeira, relating it to the interests of the Federal University of Maranhão, the School's professional body and the social agents of that community from 1980 to 2006. The process of its creation is registered to demarcate its historicity, inserting its trajectory in the historical-educational context of the emergence of gymnasiums and schools of application in Brazil; its restructuring is analyzed in order to recompose the politicaleducational conjuncture that made possible its transfer to Vila Palmeira and to demonstrate the weight of the neighborhood students' families participation in the process of acquisition of school capital for the access and permanence in the institution; it is also understood the reconstitution of the meaning of the school culture of the University School by the practices and cultural representations that come to us through the records and signs, emerging from the analyzed documentation. This study is supported in cultural history as a theoreticalmethodological approach, and makes use of bibliographical, documentary and field research. In the state newspapers as primary source, speeches that refer to this institution are identified, among them: O Estado do Maranhão, O Imparcial, Jornal Pequeno, Jornal de Hoje, O Debate, Jornal de Bolso, Jornal do Dia, Boletim Campus, Boletim Apruma Informa; as well as the school archive of the institution that contains speeches, regulations, photos as other research instruments, concomitant with the application of interviews. It highlights the way students, teachers and trainees produced and appropriated the school culture of the School, during the studied period, configuring the singular identity of the establishment.